Determining Factors in Measuring Consumators Trends for Consumption (European Journal of Marketing and Economics, 2018)
In this paper we focused on defining factors that affect in consum and in consumer behaviour. The purpose of this paper is to address the impact of Inflation and disposable income to consum, between different periods of time taken in study. We will use the consumer price index for Albanian case, to measure Inflation`s rates changes for a certain period of time, or changes in prices of goods and services included in market basket. The period that we have taken in study is from year period 2012 to 2016 , which 2015 is the base year period. The aim of this paper is to calculate the annual average of inflation rates and to analyse changes for each periods taken in the study. Also we are going to explain the relationsheep between inflation and other factors influencing in consum and consumators behaviors.
Keywords: Consume ,market basket, Inflation, Inflation rate, consumer price index